Derin Ven Trombozu ve Pulmoner Emboli - Çınaroğlu, Ayşegül (Yoğun Bakımda Tanı ve Tedavi, 2024)
Venöz tromboemboli (VTE) tanımlaması derin ven trombozunu (DVT) ve pulmoner tromboemboliyi (PTE) tanımlamaktadır.PTE’nin en sık nedeni alt ekstremitede gelişen DVT’dir. Trombofilaksiye rağmen YBU’da VTE görülebilmektedir. Hem profilakside tem tedavide kullanılan ajanlarla ilgili en büyük endişe antikoagülanlara bağlı kanamadır. Kanama riski belirlenip gerekli hastalara uygun VTE profilaksisinin sağlanması büyük önem taşımaktadır. Yoğun bakım ünitelerinde gelişen VTE’de klasik PTE klinik bulguları görülmeyeceğinden riskli hastalar belirlenip birçok yeni gelişen solunum sıkıntısı ya da hipoksemi durumunda ayırıcı tanıda akılda tutulmalıdır.Venous thromboembolism (VTE) encompasses both deep vein thrombosis (DVT) and pulmonary thromboembolism (PTE). The most common cause of PTE is DVT originating in the lower extremities. Despite prophylaxis, VTE can still occur in intensive care units (ICUs). The primary concern with both prophylaxis and treatment agents is bleeding associated with anticoagulants. Identifying the bleeding risk and providing appropriate VTE prophylaxis to necessary patients is of great importance. Since classical clinical signs of PTE may not be present in VTE developing in ICUs, it is crucial to identify high-risk patients and consider VTE in the differential diagnosis of many newly emerging respiratory distress or hypoxemia cases.